Executive functions, oral language and writing in preschool children: Development and correlations - Pazeto, Talita de Cassia Batista; Seabra, Alessandra Gotuzo; Centro, Natália Martins Dias (Paidéia (Ribeirão Preto), 2014)
Executive functions (EF) and oral language (OL) are important for learning reading and writing (RW) and for the development of other skills in preschool. The study investigated the progression and the relationships between the performances in these competences in pre-schoolers. Participants were 90 children, mean age 4.91 years, students from Kindergarten years I and II of a private school in SP, assessed, individually, with a battery with nine instruments for EF, OL, and RW. There was increase of the performances as a result of educational level for all OL and RW measures, but only for attention in the field of EF. Significant correlations were found between the measurements assessing the same cognitive domain, as well as inter-domain, although portraying a different pattern. The results indicate that OL and RW seem to develop rapidly in the course of preschool, while the EF have slower development. The fields of OL and RW, EF and RW are more interdependent, and EF and OL are relatively independent.